A genetic linkage map of Cryptococcus neoformans variety neoformans serotype D (Filobasidiella neoformans). - Marra, Robert E (2004)
To construct a genetic linkage map of the heterothallic yeast, Cryptococcus neoformans (Filobasidiella neoformans), we crossed two mating-compatible strains and analyzed 94 progeny for the segregation of 301 polymorphic markers, consisting of 228 restriction site polymorphisms, 63 microsatellites, two indels, and eight mating-type (MAT)-associated markers. All but six markers showed no significant (P < 0.05) segregation distortion. At a minimum LOD score of 6.0 and a maximum recombination frequency of 0.30, 20 linkage groups were resolved, resulting in a map length of approximately 1500 cM. Average marker density is 5.4 cM (range 1-28.7 cM). Hybridization of selected markers to blots of electrophoretic karyotypes unambiguously assigned all linkage groups to chromosomes and led us to conclude that the C. neoformans genome is approximately 20.2 Mb, comprising 14 chromosomes ranging in size from 0.8 to 2.3 Mb, with a ratio of approximately 13.2 kb/cM averaged across the genome. However, only 2 of 12 ungrouped markers hybridized to chromosome 10. The hybridizations revealed at least one possible reciprocal translocation involving chromosomes 8, 9, and 12. This map has been critical to genome sequence assembly and will be essential for future studies of quantitative trait inheritance.